Policy Research on Migration and Development - Ellerman, David (World Bank, Washington, DC, 2014)
This is a survey and analysis-with commentary-of migration issues and the related development policies for the sending countries. "Migration and development" is considered an unsettled and unresolved area for good reason. The policy issues are surprisingly deep and run to basic issues such as the nature of development as opposed to simple poverty reduction. North-north migration (between industrial countries), south-south migration (between or within developing countries), and north-south migration (from developing to industrial countries) are all covered although the paper focuses on the north-south variety. Attention is paid to the question of the dynamic mechanism underlying migration being one of convergence or divergence. Very often the policy issues push one outside what would be narrowly considered as "migration studies." For example, policies to reduce the brain drain go directly to the issue of educational reform in developing countries while policies to increase the developmental impact of remittances quickly carry one into the nature of business development itself. Ronald Dore's ideas on educational reform are outlined as a policy approach to the brain drain problem. Jane Jacobs' ideas on development are outlined in greater length as they are little known in development economics and yet directly address the policy issues raised by migration and development.